Why reform? educational policies of the 1990s, the "new teacher education project" and the results of the national evaluations - Mônica Ribeiro da Silva; Claudia Barcelos de Moura Abreu (Universidade Federal de Santa Catarina, 2008)
Brazil is experiencing a context of educational reform since the beginning of the 1990s. This paper proposed situating Brazilian education in the realm of public policies and initially conducts a brief history and contextualization of educational reform of the period. It identifies the first declarations and relates them to education conditions in the country at the time when the reform began. The paper discusses the role and guidelines of international and multilateral agencies in the formulation of local policies. It identifies the creation of interlocutors whose purpose is to promote the viability of and compliance with the goals established in the partnerships, and to give responses to the partner agents. The work demonstrates that one of the principal targets of the reform was curriculum change, used as a strategy to approximate school education to the demands made by the transformations occurred in the economy in general, and in the world of labor in particular. It reveals the consolidation of a new project for education highlighted by teacher education. Finally, it analyzes the results of this reform process, using as a reference the performance of the students gauged by means of national evaluation systems.